Reconstruction of the Executorial Power of Dispute Council Decisions in Infrastructure Projects through Harmonization of the Binding but Not Final Principle in the Indonesian Civil Law System - Anjar Kuswijanarko; R Riswadi (Journal Customary Law, 2026)
his study aims to analyze and reconstruct the binding and executory power of Dispute Board decisions in infrastructure projects within the Indonesian legal system. The main problem lies in the lack of normative recognition of Dispute Board decisions as executorial titles in civil procedural law, even though they are contractually binding under the Civil Code. This study uses a normative juridical method with a statutory and conceptual approach, and is supported by a comparative legal analysis of practices in the United Kingdom and Malaysia that have adopted the principles of Binding But Not Final and Pay Now Argue Later through special regulations. The results of the study indicate that legal reconstruction is needed through civil procedural law reform, recognition of construction adjudication mechanisms, and integration of international principles into the national legal system to increase the effectiveness of construction dispute resolution.